Synthesis and Capacitive Properties of Manganese Oxide Nanoparticles Dispersed on Hierarchical Porous Carbons. (1st June 2015) - Zhang, Yafei; Zhang, Chuanxiang; Huang, Guangxu; Xing, Baolin; Duan, Yuling
Graphical abstract: Highlights: By contrast with template methods, HPCs are obtained by activation of humic acid, which is simple and cost-effective. HPCs are rich in oxygen-containing functional groups, which allow the formation and uniform anchoring of fine MnO2 via strong chemical interactions between the functional groups of HPCs and the nanomaterials. Abstract: A growing manganese dioxide (MnO2 ) nanoparticles on hierarchical porous carbons (HPCs) is conducted via a simple route starting with KMnO4 and ethanol aimed to enhance the electrochemically active surface area of MnO2 . It is found that these MnO2 nanoparticles are uniformly grown on the external surface of the HPCs and still maintain hierarchical porous structure, yielding a composite electrode showing good electron transport, rapid ion penetration, fast and reversible Faradic reaction when used as supercapacitor electrode materials. HPCs–MnO2 composite displays the specific capacitance as high as 167 F g −1 and 192 F cm −3 in 3 M KOH aqueous electrolyte and 94 F g −1 and 113 F cm −3 in 1 M tetraethylammonium tetrafluoroborate/propylene carbonate (Et4 NBF4 /PC) organic electrolyte. Furthermore, it also exhibits a superior cycling stability with 96% retention of the initial specific capacitance after 1000 cycles and stable Coulombic efficiency of 99% in 3 M KOH measured using the galvanostatic charge–discharge technique.